THE INVISIBLE CONFLICT: DOMESTICATION VERSUS FOREIGNIZATION IN THE TRANSLATION OF CULTURAL IDIOMS - Umaraliyev Mukhriddin (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the dichotomy between domesticating and foreignizing strategies in literary translation. Drawing on Lawrence Venuti’s theories, the paper analyzes how translators navigate the "cultural gap" when transferring idiomatic expressions from a source language (SL) to a target language (TL). It argues that while domestication aids readability, foreignization is essential for maintaining the cultural "otherness" of the text.